Power in the international trading system: Trump administration risks destroying world trade order - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2018)
The international trading system is in flux. A spiral of protectionism threatens to expose the limits of the WTO's ability to protect against abuses and prevent trade wars. And the reason for this is astonishing: The US Administration believes that the existing rules - which the Americans themselves played a leading role in writing - disadvantage the United States. Currently the Trump Administration is working hard to dismantle the system.
Keywords: 320